A triterpene glochidon from Phyllanthus debilis: Isolation, computational studies, and antidiabetic activity evaluation. (September 2021) - Verma, Amita; Pathak, Prateek; Rimac, Hrvoje; Khalilullah, Habibullah; Kumar, Vikas; Grishina, Maria; Potemkin, Vladimir; Ahmed, Bahar
Abstract: Diabetes mellitus (DM) is a metabolic disease characterized by a dysfunction of pancreatic β -cells. It is well documented that oxidative stress and inflammation increase the severity of DM and its complications can be fatal. Research shows that certain triterpenoids can play a significant role in the inhibition of oxidative stress and inflammation. In this study, we isolated a novel triterpenoid glochidon, from the Phyllanthus debilis Klein ex Willd. (Family: Phyllanthaceae) using traditional column chromatography and characterized using spectroscopy. The compound was tested for antidiabetic activity through in vitro and in vivo experiments followed by computational studies. In vitro assays confirmed that glochidon has a dose-dependent moderate inhibitory activity against α -glucosidase, α -amylase, DPP-4, and PPAR- γ . Docking and MD results also show that glochidon has moderate efficacy to inhibit DPP-4 and PPAR- γ, when compare to standard agents and a strong tendency to interact with the GLUT1 protein. Computational ADME profiling determined that glochidon has excellent characteristics to act as a lead hypoglycemic compound. Results of the in vivo experiments show that at a dose of 20 mg/kg, glochidon significantly increased body weight, plasma insulin, high-density lipoprotein levels, and other biochemical markers. Additionally, it lowered the blood glucose, total cholesterol, triglycerides, low-density lipoprotein, and very low-density lipoprotein. Graphical abstract: Image 1 Highlights: A novel triterpene, glochidon, is isolated from Phyllanthus debilis . In vivo studies illustrated that glochidon can effectively reduce/plasma blood glucose, and effectively participate in pancreatic β cells repair. Computational studies showed that glochidon has a modest to strong affinity to interact with DPP-4, PPAR-γ, and GLUT-1 proteins.